Tree Communities and Aboveground Biomass in the Submontane Zone of Ketambe Resort, Mount Leuser National Park, Aceh - Taufikurrahman Nasution; Muhammad Efendi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Abstract: Mount Leuser National Park is one of the largest conservation areas and plays important ecological and economic functions. To support forest management, it is important to gain current vegetation data. The sampling method of a 0.1 hectare plot was carried out on two sampling sites in the submontane zone of Ketambe Resort, Mount Leuser National Park, Aceh. The diversity of trees was not significantly different, while species composition was different. Site one was dominated by Syzygium spp. and Shorea platyclados, while site two was dominated by Altingia excelsa and Bridelia glauca. Lauraceae, Myrtaceae, and Dipterocarpace families dominated in both sites. Tree structures formed three strata and showed a good capacity for forest regeneration. The aboveground biomass of site one was higher than site two due to the presence of more large trees. Pioneer species, cultivated plants, a low average wood density, and low aboveground biomass indicated secondary forest characteristics in both sites. Abstrak: Taman Nasional Gunung Leuser merupakan salah satu kawasan konservasi yang terluas dan memiliki fungsi ekologi dan ekonomi yang penting. Data vegetasi terkini penting didapatkan untuk mendukung pengelolaan hutan. Metode sampling dengan plot 0.1 hektar dilakukan di dua lokasi pada zona submontana Resort Ketambe, Taman Nasional Gunung Leuser, Aceh. Keanekaragaman jenis pohon tidak berbeda secara nyata sementara komposisi jenis berbeda. Lokasi satu didominasi oleh Syzygium spp. dan Shorea platyclados, sementara lokasi dua didominasi oleh Altingia excelsa dan Bridelia glauca. Suku Lauraceae, Myrtaceae dan Dipterocarpace mendominasi pada kedua lokasi. Struktur pohon membentuk tiga strata dan menunjukkan kemampuan regenerasi hutan yang baik. Biomassa pohon di atas permukaan pada lokasi satu lebih tinggi dibandingkan lokasi dua karena lebih banyaknya pohon berukuran besar. Jenis pionir, tanaman budidaya, rata-rata berat jenis kayu dan biomassa di atas permukaan yang rendah mengindikasikan karakteristik hutan sekunder pada kedua lokasi.